The remarried empress. 8 - Alphatart (Novelist); HereLee (Mangaka) (Ize Press, 2024)
Sovieshu has discovered that Navier overheard his plan to divorce her, and he's furious! Is this the reason everything went to ruin?! Had Navier not gotten the wrong idea, she would've never remarried Heinrey in retaliation, right? Convinced of his new truth and determined to set things straight, Sovieshu invites Navier to his wedding ceremony. But with feelings flourishing between Heinrey and Navier and Rashta's breaking point swiftly approaching, the reunion Sovieshu gets may be a far cry from the one he imagined--.